CCAFS midline synthesis – Ghana. Assessment of changes at household, village and organization levels since the 2011 CCAFS baseline surveys - Ouédraogo, Mathieu; Houessionon, Prosper; Cramer, Laura K.; Partey, Samuel T.; Zougmoré, Robert B.; Thornton, Philip K.; Jasaw, Godfred Seidu; Buah, Saaka S.J.; Riba, Alex; Barahona, Carlos (2019)
In 2011, CCAFS carried out baseline surveys (household survey, a village study and an organizational survey) in 21 research sites across 17 countries within its five focus regions, using standardized baseline tools in each site. Seven years after the implementation of the baseline studies, the CCAFS program carried out surveys again in Lawra-Jirapa, Ghana as a test case to help determine whether a midline assessment in other sites would be worth the substantial investment that will be needed. The objective of the CCAFS midline surveys was to assess what kinds of changes have occurred and whether these changes are helping the households and villages adapt to and mitigate climate change. It also provided information at the village level about some basic indicators of natural resource utilization, organizational landscapes, information networks for weather and agricultural information, as well as mitigation baseline information, which can be compared across sites and monitored over time. The same tools were used with a few improvements to ensure comparability with the data collected in 2011. This info note provides a synthesis of the changes at the household, village and organizational levels emphasizing major indicators that have changed.